PRAKTEK MERAWATGIGI PADA ANAK - Sri Mulyati (Asian Journal of Innovation and Entrepreneurship, 2013)
The habit of brushing your teeth is a healthy habit that needs to be done to keepthechild's teeth and mouth. Moreover, when the child's age is increasing and childrenbegan to consume a variety of foods, including sweet foods such as fruit juice, sweetsand chocolates. Sweet foods as it can damage dental health of children and can causeproblems cavities, porous black teeth and bad breath bad. Therefore, it is important forparents to teach how to brush their teeth regularly to children. Children previouslybeen aware of the necessity for brushing their teeth but they do not know how to brushteeth properly, so the program is deemed necessary to be implemented. The purpose ofthis activity is to familiarize children to brush his teeth from as early as possible and toprovide knowledge about how to brush teeth properly. Implementation of theprogramon child dental care practices include process steps lectures, discussion, and practice.The success of this activity is seen from the practice of dental care program participatedin these children by all kindergarten children.